Investigating the effects of closed kinetic chain exercises on joint position sense, functionality, range of motion, and pain in individuals with distal radius fracture: a randomized controlled trial - Burak Menek; Emre Dansuk (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Distal radius fractures (DRFs) are common upper extremity injuries that often result in pain, limited mobility, and impaired proprioception. While conventional rehabilitation typically targets range of motion (ROM) and strength, closed kinetic chain (CKC) exercises may offer additional benefits by enhancing neuromuscular control and proprioception. This study aimed to investigate the effects of CKC exercises on pain, function, proprioception, and ROM in individuals recovering from conservatively treated DRFs. Methods Forty individuals with conservatively treated DRF were randomly assigned to either the CKC group (n = 20) or the conventional group (CP) (n = 20). Both groups participated in a six-week rehabilitation program after cast removal. Outcome measures included Visual Analog Scale for activity-related pain (VAS-Activity), active ROM (flexion/extension), Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaire, and joint position sense (JPS). Results Both groups demonstrated significant improvements in all outcomes after six weeks (p < 0.05). However, the CKC group showed greater improvements across all domains. Specifically, JPS improved by 6.75° ± 3.21° in the CKC group compared to 4.95° ± 2.88° in the CP (Cohen d = 2.05), exceeding the minimal clinically important difference (MCID) of 5°. DASH scores decreased by 37.11 ± 10.27 points in the CKC group and 18.15 ± 9.61 in the CP (Cohen d = 3.46 vs. 1.77), both surpassing the 10-point MCID. Wrist extension increased by 44.00° ± 13.01 (CKC) versus 30.10° ± 11.42 (CP) (p < 0.001), and flexion by 52.50° ± 14.81 (CKC) vs. 39.20° ± 14.21 (CP) (p < 0.001). VAS-Activity scores improved by 5.35 ± 2.04 (CKC) and 3.40 ± 1.52 (CP) (Cohen d = 2.60 vs. 1.72), both exceeding the 2-point MCID threshold. Conclusions CKC exercises were more effective than conventional therapy in improving proprioception (measured by joint position sense), upper extremity function (assessed by the DASH questionnaire), pain levels (VAS-Activity), and wrist ROM in individuals undergoing DRF rehabilitation. These findings from a randomized controlled trial support the integration of CKC exercises into standard physiotherapy programs for this population. Clinical trial registration NCT06811480. Trial registration Prospectively registered in the ClinicalTrials.gov registry (NCT06811480) on 06/12/2024.